Philippine medical thesaurus on anatomy animal structures, sense organs and food beverages in Pangasinan - Franco, Harold T. 1982- (2004.)
The incorporation of switching language in the construction of Philippine Medical Thesaurus has made all the information contained in the Philippine Medical thesaurus accessible to people of different country and languages. Although thesaurus serve as a great tool for information storage, management and retrieval, the inclusion of the switching language like conversion of all the terms in the thesaurus from one language to another like that of Pangasinan could create a lot of problem. With this idea, how could the Philippine Medical Thesaurus in Anatomy : Animal Structures, Sense Organs and Food and Beverages in Pangasinan be beneficial and can cater to the information needs of its end-users? Being a succeeding work in Philippine Medical Thesaurus, it delivers the problem with the resolution of constructing a thesaurus of carefully defined terms and terms that are properly examined to assure the end-users that the terms are of good source of information. During the study, different problems have kept arise but various solutions to these problems are carried out in order to resolve such.
The utilization of the two approach in the thesaurus construction: the top-down and bottom-up approach, was successfully done in order to meet the end of the study in which is to create an information tool which could cater to the information-retrieval needs of the end-users. Terms are carefully sifted, relationships were well established and organization has been made for the end-users to get a coherent and clear view of the thesaurus.
This study, having translated 37 (included here were the terms hoof and claw which was counted as one) terms out of 53 terms downloaded from MeSH, 2004 for the sub-facet Animal Structures, 37 out of 94 terms were translated on the sub-facet Sense Organs and lastly, on the Food and Beverages sub-facet, 79 terms were translated out of a 125 terms summing up to 153 terms translated all in all. With an addition of 3 additional terms [checked] out by the author, could start a way wherein creating a thesaurus of a switched language could not impossibly be attained.
Vita
Undergraduate thesis (B.L.I.S.)--University of the Philippines, Diliman.
Keywords: Subject Heading -- Medicine -- Philippines; Animals -- Anatomy; Sense organs; Food; Beverages; Pangasinan language -- Medical Pangasinan